Breastfeeding Characteristics Are Associated with Minor Changes in the Human Milk Microbiome - Ruomei Xu; Mark P. Nicol; Ali S. Cheema; Jacki L. McEachran; Sharon L. Perrella; Zoya Gridneva; Donna T. Geddes; Lisa F. Stinson (Proceedings)
Human milk has a microbiome that contains a wide variety of typical oral and skin bacteria, suggesting that the bacterial communities in the infant oral cavity and maternal skin contribute to the development of the human milk microbiome [...]